Trihalomethanes in Lisbon Indoor Swimming Pools: Occurrence and Determining Factors - Silva, Z. (2012)
Inclui artigo publicado em: Proceedings of the 4th International Conference of Swimming Pool & SPA(ICOEH), 2011, Porto: 40-50